Sputter-etching treatment of proton-exchange membranes: Completely dry thin-film approach to low-loading catalyst-coated membranes for water electrolysis. (21st August 2020) - Hrbek, Tomáš; Kúš, Peter; Yakovlev, Yurii; Nováková, Jaroslava; Lobko, Yevheniia; Khalakhan, Ivan; Matolín, Vladimír; Matolínová, Iva
Abstract: Simultaneous plasma etching of a proton-exchange membrane (PEM) and deposition of a cerium oxide layer during reactive magnetron sputtering leads to the formation of a pronounced fiber-like structure on its surface. The level of structural porosity can be adjusted by varying the working pressure during the process. A PEM treated this way can be subsequently coated with a thin layer of iridium, forming an anode-side catalyst-coated membrane (CCM) for applications in water electrolysis. Due to the significantly enlarged surface of the membrane, there is no necessity for any additional, potentially corroding, support nanoparticles to achieve efficient in-cell operation. Moreover, utilizing a rotatory frame-shaped substrate holder and a multitarget deposition apparatus, the sputter-etching process can be used in the preparation of a full anode/cathode thin-film CCM in a single vacuum entry. This structure yields remarkable performance characteristics in an electrolyzer cell, considering its low combined noble metal loading of just 220 μg cm −2 . Using this completely dry process for CCM manufacturing may facilitate efficient large-scale future production. Graphical abstract: Image 1 Highlights: Surface of proton-exchange membrane was modified by dry sputter-etching process. Created fiber-like structure can serve as a catalyst support for PEM-WE applications. Level of porosity can be tuned by varying the working pressure during the treatment. CCM with modified PEM and thin-film catalysts was prepared solely by dry technique. High performance was achieved with the combined Pt + Ir loading of just 220 μg cm −2 .